Новый вид белокровной щук из Южного океана - Мейснер, Э.Э. (Вестник зоологии, 1974)
﻿ New fish species Chaenichthys velifer sp. n. from Antarctica differs from the relative Ch. rhinoceratus Richardson, 1844 in greater body height (its length contains the height less than 5 times), ray quantity and ID form, structure of the lower lateral row of bony plates and opercular spine, vertebra quantity, colour and pattern of drawing. These characters serve a basis of the identification key for the species of genus Chaenichthys. Ch. velifer inhabits the area near island Kergelen at depths to 150 m. Its food is fish and Cephalopoda.